A multi-modal, web-based inquiry learning environment on Genetically Modified Organisms - Herodotou, Christothea; Iolie Nicolaidou; Hadjichambis, Andreas Ch.; Terzian, Frederiki; Kafouris, Dimitris; Kyza, Eleni A. (My University, 2011)
A multi-modal, web-based inquiry learning environment (LE) on Biotechnology and Genetically Modified Organisms (GMOs) is the focus of this presentation. The LE has been developed for use in science education as a means to raise students’ interest in socio-scientific problems and create a bond between the scientific enterprise and human life through the use of new information technologies. The LE was built around the idea of software-based scaffolding, the role of which is crucial for successful reflective inquiry and synchronous and asynchronous collaboration among students. A design-based approach was followed for the development of the LE; the LE was designed by a Local Working Group (LWG) in Cyprus, piloted, redesigned and re-enacted in a high school class. The analysis of pre and post tests administered to students during the LE’s reenactment demonstrated the effectiveness of the intervention; students’ conceptual understanding and credibility skills were significantly improved by the end of the enactment. Such approaches can become the catalyst for making science education more attractive and appealing to students’ learning needs
Keywords: Genetically Modified Organisms; Web-Based Inquiry Learning Environments; Web-based inquiry; Multi-Modal Learning